Atmospheric initial conditions and the predictability of the Arctic Oscillation. Issue 4 (26th February 2015) - Stockdale, Timothy N.; Molteni, Franco; Ferranti, Laura
Abstract The Arctic Oscillation (AO) is the leading mode of variation in the northern hemisphere winter circulation. Despite its importance for winter temperatures, seasonal forecast models typically suggest that its predictability is low. Nonetheless, we show that an operational forecast model has high skill in predicting the AO, with a correlation of 0.61 for the period of 1981–2010. Experimentation covering a recent 8 year high‐skill period demonstrates the predictability of the model AO to be dominated by atmospheric initial conditions, although surface forcing does have increasing influence later in the winter. Results suggest that the stratosphere is an important carrier of model predictability during the early winter. These results challenge the conventional paradigm of surface forcing being the dominant source of predictability on seasonal time scales but are compatible with the results showing stratospheric influence on winter circulation. They also suggest that model representation of stratospheric to tropospheric coupling needs urgent improvement.